DEMISTIFIKASI MEMUDARNYA PERAN NEGARA DALAM NEOLIBERALISME (Perdagangan Bebas dan Konflik Antar Negara dibawah Rezim WTO) - Muhammad Chairil Akbar (GLOBAL INSIGHT JOURNAL, 2016)
World economic order after the ratification of GATT (General Agreement On Tarrifs and Trade) shows some contractions and a number of controversies. The broadening of trade agenda in Uruguay round was a new phase of agreement among the countries. Ministerial meeting 1986 produced a declaration called Punta del Este. This consensus creates the establishment of WTO as the only multilateral institution to mediate any cooperations of global trade. WTO itself palys its role to sustain and make sure that the agenda of trade liberalization runs optimally. Nevertheless, amids the euphoria of trade liberalization discourse, some problems and polemic come up. They appear due to inconsistency of developed countries which implement protectionism policy on their some sectors of trade. Third world group then build a coalition to refuse every form of deception in free trade policy. This condition has caused the emergence of internal friction in the body of WTO In this paper, the author will try to analyze and explain the dynamic of trade liberalization policy among the countries after the establishment of WTO. The main focus are on 2 questions, first, why is there conflict of interest in WTO?, and second, how is the dialectical relation of protectionism with free trade system between developed countries and developing countries?  Subsequently, we will obtain a hypothese that market liberalization is never fully implemented instead. Doctrine of free market and the elimination of trade handicaps are not executed consistently by developed c,ountries. Third world countries even tend to be dictated and suppressed to eliminate all kinds of trade handicaps. This handicap include some regulations like subsidy, tarrief,quota, or taxation. So the consequence is the destruction or domestic market in third world due to their incompetence of capital against MNC and developed countries. Market liberalization under neoliberalism can be stated as a new form of Unilateralism in Economy. Stronger and more advanced countries manage to impose their national interest on many trade agreements. The massive integration of world economy has created disparity and imbalanced competition. World is divided by a world gigantic power of capital which exploit third world. Through the mechanism of capital and trade liberalization, our reality si underpinned by domination and monopoly.  Globalization of economy has become a trap for south countries which keeps maintaining wealth accumulation only to few capitalist and developed countries This writting aims to problematize the inconsistent rules implementation within WTO in term of trade policies among countries. Trade liberalization has been mostly taken for granted which in turn covers up certain form of protectionism on some strategic commodities. It has sparked debates about the role of WTO whether it can truly liberalize trade policies or it has surrendered to the strong and  significant role of government intervention in advanced countries.